RETROPERITONEAL LYMPH NODE DISSECTION: CASE SERIES AND CONTEMPORARY LITERATURE PERSPECTIVES - Nusrat, Nadeem Bin; Rehman, Assad ur; Muhammad, Shujah; Zafar, Nauman; Aslam, Asadullah; Arshad, Hassan; Khan, Yasir; Imtiaz, Sarmad; Arshad, Moin; Chaudhary, Aadil; Imtiaz, Saira (Journal of Ayub Medical College Abbottabad, 2026)
Purpose: Retroperitoneal lymph node dissection (RPLND) remains a part of the management of men with metastatic germ cell tumours and is infrequently performed. The purpose of this study was to review clinical outcomes and complications of RPLND performed at Pakistan Kidney and Liver Institute & Research Center (PKLI & RC), Lahore, using data of patients who underwent the procedure between August 15, 2022, and July 16, 2024, as well as compared the results with the previous studies. Materials and Methods: This study is a retrospective case series analysis of all patients who had RPLND at PKLI & RC in the given time frame. Patients' demographics and medical history, surgical details, postoperative course, and follow-up data were recorded on a structured questionnaire. Results: Five patients who were treated by RPLND were enrolled in the study. The average age was 30. 40 ± 3. 98 years on average, and the average length of stay in surgery was 256. 00 ± 85. 47 minutes. A postoperative complication was intraoperative blood loss which required transfusion in one case. Epidural analgesia was the main approach that was utilized in managing pain. The mean time spent on hospital visits was 7. 20 ± 1. 48 days. Several pathologies were seen including the mature cystic teratoma, teratoma and the mixed germ cell tumor. Conclusion: It was observed that RPLND at PKLI & RC usually yielded good results with manageable complications after surgery. In view of the above findings, this study provides useful information on the procedural aspects and the postoperative management of RPLND in order to enhance patient care in the future. For these reasons, it is recommended that subsequent research be conducted with larger sample sizes as a means of cross-checking these findings and enhancing understanding of potential long-term effects.